Typography Talks: Influencing Vintage Anemoia and Product Safety Perceptions with Vintage Typography - Kulczynski, Alicia; Hook, Margurite (Journal of Marketing, 2024)
Drawing from the concept of anemoia, the authors propose a new typology of nostalgia called vintage anemoia. Vintage anemoia encompasses consumers’ positive and nostalgic response to vintage cues, regardless of specific historical periods or individual lived experiences. Through a series of seven studies, the authors demonstrate that vintage typography, by evoking feelings of vintage anemoia, can enhance consumer perceptions of product safety. This effect has positive downstream consequences on key marketing outcomes, including brand attitude, purchase intention, and willingness to pay. Furthermore, the effect of vintage anemoia on product safety perceptions remains unaffected by whether product safety information indicates that a product is safe or unsafe. However, the effect diminishes when an explicit indexical cue (year of establishment) is utilized or when promoting futuristic products. The findings contribute to the existing body of knowledge in marketing and provide insights for marketers on leveraging vintage typography as a strategic tool for creating emotional connections with consumers and enhancing perceptions of product safety.